Implikasi Hukum pada Perjanjian Kerjasama Bisnis Waralaba dalam Hukum Perdata - Noviriska; Dwi Atmoko (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
In general, a franchise is known as a franchise, which means an agreement or contract (contract) between a supplier and a retailer or wholesaler, stating that the former grants the latter the right to trade its products, with conditions agreed upon by both parties. In relation to granting permits and fulfilling obligations, the franchisee or franchise business system is the use of a well-known brand. This system is considered profitable because it is a trading system that is immune to economic recession. Management and the level of profitability of the company can be stable, so that it can provide mutual benefits between the parent company and the company that cooperates with the franchising system. In addition, the more companies that carry out franchises by opening new branches in the area, the faster the business being run will be known because the public will easily obtain the desired product. The franchise system is basically a method of market expansion carried out by companies that are already established or well-known and have a name.This system is highly suitable for business development strategies because companies are not only able to develop their businesses in their home country but also expand their reach worldwide. The implications of a franchise agreement are extensive, encompassing legal, financial, and operational implications for both parties: the franchisor and the franchisee. Legally, this agreement is binding and regulates rights and obligations in detail, while financially, there are obligations to pay royalties and other fees. Operationally, the franchisee receives system support and training, while the franchisor is responsible for providing such support